AB1332-HPR ASSESSING THE PATIENT EXPERIENCE OF LUPUS NEPHRITIS: DEVELOPMENT OF A CONCEPTUAL MODEL AND REVIEW OF EXISTING PATIENT-REPORTED OUTCOME (PRO) MEASURES. (2nd June 2020) - Berry, P.; Burrows, K.; Hall, R.; Gater, A.; Bradley, H.; Ward, A.; Tolley, C.; Delong, P.; Hsia, E. C.
Abstract : Background: Lupus nephritis (LN) is an autoimmune disease characterized by inflammation of the kidneys as a result of systemic lupus erythematosus (SLE). Approximately 50% of SLE patients will develop LN, which is considered to be one of the most severe manifestations of SLE and the leading cause of morbidity and mortality in SLE. While there is ample existing evidence on disease experience and PROs used in extra-renal SLE, little research has been done in LN. Qualitative interviews with patients can help identify concepts that are both important and relevant to the patient. In order to effectively evaluate treatment benefit, it is critical that PRO measures used to assess such concepts and define clinical trial endpoints are fit for purpose and have strong evidence of content validity in the specific context of use. Objectives: The objective of this study was to understand the patient experience of LN and to identify and characterize the signs and symptoms of LN and their impact on health-related quality of life (HRQoL) through the development of a disease-specific conceptual model. This model was then used to evaluate the content validity of existing PRO measures available for use in LN. Methods: A structured literature search was conducted in Medline, Embase and PsycINFO to identify qualitative research articles documenting the patient experience of LN. PRO measures developed or commonly used to assess patient experiences of LN were also identified. Semi-structured concept elicitation interviews were conducted with 15 adult patients in the US with a clinician-confirmed diagnosis of LN (defined in accordance with established clinical guidelines). Supplementary qualitative data were also collected from a review of publicly available online blogs/forums. Findings were used to inform the development of a conceptual model detailing the impact of LN signs, symptoms and HRQoL and evaluate the validity of existing measures used within LN. Results: Searches revealed a paucity of qualitative research conducted with LN patients, supporting the need for prospective research in LN. Consistent with existing literature in SLE, the core signs and symptoms identified from the qualitative literature review, interviews and blog/forum review included joint pain, fatigue, joint stiffness, swelling (particularly in the extremities) and skin rashes. LN patients also reported urinary frequency, urgency, foamy urine and blood in their urine. Disease impact on physical functioning, activities of daily living, emotions, social life, work/finances and sleep were reported. PRO measures commonly used to evaluate patient experiences in LN included the SF-36, LupusQOL, LupusPRO, SLE Symptom Checklist, KDQoL and KSQ. Conceptual mapping of instruments against the newly developed conceptual model (Figure 1 ) highlighted that no single measure provides a comprehensive assessment of all symptoms/impact important to LN patients. Furthermore, items are largely focused on impact of symptoms with few items on symptom severity. Conclusion: The presentation of signs and symptoms in LN patients appears similar to those reported in extra-renal SLE populations, with the addition of swelling and urinary symptoms. Qualitative research with LN patients guided the development of a comprehensive LN conceptual model outlining the disease experience from the patients' perspective. These insights can be useful to inform PRO measurement strategies for clinical trials in LN. Acknowledgments: With thanks to Dr. Betty Diamond and Dr. David Wofsy for their collaboration and helpful insights Disclosure of Interests: Pamela Berry Employee of: Janssen, Kate Burrows Consultant of: Adelphi Values a health outcomes research company commissioned by Janssen to conduct the research reported in this abstract, Rebecca Hall Consultant of: Adelphi Values a health outcomes research company commissioned by Janssen to conduct the research reported in this abstract., Adam Gater Consultant of: Adelphi Values a health outcomes research company commissioned by Janssen to conduct the research reported in this abstract, Helena Bradley Consultant of: Adelphi Values a health outcomes research company commissioned by Janssen to conduct the research reported in this abstract, Amy Ward Consultant of: Adelphi Values a health outcomes research company commissioned by Janssen to conduct the research reported in this abstract, Chloe Tolley Consultant of: Adelphi Values a health outcomes research company commissioned by Janssen to conduct the research reported in this abstract, Patricia Delong Employee of: Janssen, Elizabeth C Hsia Shareholder of: Johnson & Johnson, Employee of: Janssen Research & Development, LLC